Spoken corpora and corpus-informed language pedagogy: Implications arising from research - Kızıl, Aysel Şahin (My University, 2017)
Defined in its broadest sense as large databases illustrating actual language use, corpora have proved to be influential in enabling researchers to develop innovative perspectives not only in linguistics but also in a number of applied disciplines including speech recognition or machine translation. One discipline on which language corpora have tremendous effect is the field of language teaching. Although the research on corpus-informed language pedagogy is mostly dominated by the findings through the analysis of written corpora, it is now widely acknowledged that spoken corpora which are slower to emerge compared with written corpora could also offer great potential for language pedagogy. This study sets out to review the major findings from the research on spoken corpora and current instructional treatments with the purpose of discussing the ways of expanding spoken-corpus-informed pedagogy to language classrooms.
Bildiri - Yayımlanmış
Keywords: English language teaching; Pedagogical implications; Spoken corpora; Corpus-informed pedagogy